Overestimation of medical consequences of low-dose exposures to ionizing radiation - S. V. Jargin (Сибирский научный медицинский журнал, 2022)
Overestimation of medical consequences of low-dose exposures to ionizing radiation contributes to the strangulation of nuclear energy production. Several examples of the overestimation are discussed here: the Chernobyl accident, East Urals Radioactive Trace and Semipalatinsk Nuclear Test Site. Results of certain studies of Chernobyl-related malignancies should be reassessed taking into account that some cases, classified as aggressive radiogenic cancers, were in fact late-stage malignancies. Associations of various markers with the tumor progression can become a field for future research and re-interpretation of data obtained in studies comparing malignancies from different regions. Reported correlations between low-dose exposures and non-malignant diseases call in question the cause-effect character of such correlations for cancer reported by the same and other researchers. The correlations may have been caused or influenced by bias, in particular, the dose-dependent selection and self-selection: individuals with higher dose estimates would be on average more motivated to undergo medical checkups and given more attention. Therefore, diagnostics tend to be more efficient in people with higher doses. Lifelong animal experiments are a promising approach to the research of dose-response relationships.